Dictionary of Contact Allergens - Lepoittevin, Jean-Pierre; Coz, Christophe J. (Springer Berlin Heidelberg : Imprint: Springer, 2007)
The Dictionary of Contact Allergens is a helpful guide for familiarizing the reader with the structures of chemicals implicated in contact dermatitis. Each molecule is described together with its principal name for classification. The most important synonyms, the Chemical Abstract Service (CAS) registry number, which characterizes the substance and its chemical structure, and the relevant literature references are also listed. Further, the reader will find a unique chapter on patch testing with the patient's own products. This guide is a "must-have" for any physician involved with the diagnosis and treatment of patients with contact dermatitis and allergic skin disease.